A Literature Review on: Smart Bottle using IOT - Vishwakarma, Sonali; Goud, Anushree (International Journal of Computer Sciences and Engineering, 2019)
In this omnipresent IT world even the non-living items communicate amongst themselves and smartly react depending on dynamic situations. IOT (Internet of Things) is a technology which is highly emerging that understands and conceptualizes this nature of computing. The paper gives a brief review on water bottle using IOT technology. Water is very important part of human life. Variety of parameters effect the quality of water. The smart bottle monitors these parameters constantly in real time using input sensors, the system then processes the input data and performs necessary actions if required using actuators. This system will be helpful for health conscious human beings in today’s life. This system can also be greatly utilized in healthcare domain where extra care needs to be taken in all aspects.